2015
DOI: 10.1159/000433549
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Vestibular Hypofunction: Challenges in Establishing the Diagnosis in Adults

Abstract: Bilateral vestibular hypofunction (BVH) probably represents a heterogeneous disorder with different types of clinical pictures, with and without vertigo. In spite of increasingly sophisticated electrophysiological testing, still many challenges are met when establishing a diagnosis of BVH. Here, we review the main challenges, which are a reflection of its often difficult clinical presentation and the lack of diagnostic standards regarding the implementation and interpretation of vestibular tests. These challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 138 publications
2
109
0
10
Order By: Relevance
“…Outside specialized balance centers, the diagnosis of BVL is often delayed or missed (153), because the characteristic symptoms of postural imbalance and oscillopsia (154156)—often without vertigo—are not recognized. Once the suspicion has been raised, the clinical diagnosis is often straightforward based on three simple clinical bedside tests: the HIT, dynamic visual acuity, and the Romberg test on rubber foam (157).…”
Section: New Clinical Disease Patterns Emerging From 3d Video Head Immentioning
confidence: 99%
“…Outside specialized balance centers, the diagnosis of BVL is often delayed or missed (153), because the characteristic symptoms of postural imbalance and oscillopsia (154156)—often without vertigo—are not recognized. Once the suspicion has been raised, the clinical diagnosis is often straightforward based on three simple clinical bedside tests: the HIT, dynamic visual acuity, and the Romberg test on rubber foam (157).…”
Section: New Clinical Disease Patterns Emerging From 3d Video Head Immentioning
confidence: 99%
“…Unfortunately, the picture is completely different for other conditions. The handicap suffered by patients with a complete loss of the vestibular function is significantly underestimated and the pathway to diagnosis is full of hurdles [46,64]. However, recent studies have unambiguously revealed that the complete loss of the vestibular function has a dramatic impact on the quality of life of affected patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to blurred vision (oscillopsia) and impaired balance and spatial orientation (2, 3). A significant decrease in quality of life and considerable high physical and socio-economic impacts have been reported (4, 5).…”
Section: Introductionmentioning
confidence: 99%